PSST! (Pamilya, and sisto sayron 'ta!) design and development of a health communication plan to improve knowledge on schistosomiasis and mass treatment among the residents of Brgy. Kapatungan, Trento, Agusan del Sur - Reyes, Margarette G.; Glova, Nelfa M. (2019)
The results of the formative evaluation in the initial phase of this research revealed that the respondents exhibited low knowledge on Schistosomiasis and mass treatment. Given this condition, this study aimed to design and develop a comprehensive health communication campaign plan to improve the level of understanding on Schistosomiasis and mass treatment among the residents of Brgy. Kapatungan, Trento, Agusan del Sur. To realize the primary objective of this study, the researcher designed messages, sources, and channels that are appropriate for the target audience in the health communication campaign plan. The design and development of the messages, sources, channels are grounded o the findings of the formative evaluation which generally explored the sociodemographic profile, the sources of information on Schistosomiasis and mass treatment, and the media preference and information needs of the target audience.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019